Immature Teratoma after Three Laparoscopic Resections for Mature Cystic Teratomas - Kazuhiro Nishioka; Naoto Furukawa; Taketoshi Noguchi; Hirotaka Kajihara; Kiyoshige Horie (Hindawi Limited, 2014)
We report a case in which an immature teratoma developed following three previous resections for mature cystic teratomas. The patient was a 26-year-old nulliparous woman with a regular menstrual cycle. Twelve years earlier, she had consulted a pediatrician for complaints of lower abdominal pain. Bilateral cystic teratomas were suspected and she underwent a left salpingo-oophorectomy and a right cystectomy laparoscopically, and bilateral mature cystic teratomas were diagnosed histologically. She underwent a right cystectomy twice afterwards and mature cystic teratomas were diagnosed. Three years after the third surgery, a regular checkup performed annually for ovarian cyst recurrence revealed a 9.3 cm ovarian cyst by ultrasonography without marker elevation or complaint of symptoms. Magnetic resonance imaging (MRI) showed a 10 cm multilocular cyst, including a part with heterogeneous medium and high-signal intensity on T2-weighted images, which revealed enhancement on dynamic contrast-enhanced MRI unlike the previous images. Ovarian tumors, including immature teratomas and malignancy, were considered. She had a strong wish to undergo laparoscopic surgery. She was diagnosed with an immature teratoma, grade 1 of the right ovary. Although the frequency of recurrence of immature teratomas after resection of mature cystic teratomas is very low, regular checkups are necessary because there may be no associated symptoms.